Fuel cell electrodes, catalyst coated membranes, fuel cells, and methods for making fuel cell electrodes and catalyst coated membranes
By actively adding chloride ions to the fuel cell electrode, the catalyst instability problem caused by chloride ions is solved, and the long-term stability and high-performance operation of the fuel cell electrode are achieved.
Patent Information
- Application Number
- JP2024555167
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-21
- Filing Date
- 2023-03-15
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-03-15
Smart Images

Figure 2025509763000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to fuel cell electrodes, catalyst coated membranes, fuel cells, and methods of making fuel cell electrodes, and methods of making catalyst coated membranes. [Background technology]
[0002] It is known in the art that halide ions, and here particularly chloride ions, can reduce the functionality or long-term stability of membrane electrode assemblies for fuel cells. Halide ions can be introduced into the membrane electrode assembly in a variety of ways, for example, by using halide-containing precursor compounds for catalysts used in the electrodes of the membrane electrode assembly, such as HPt(Cl) .
[0003] Under practical operating conditions, MEAs undergo potential cycling, i.e. alternating high and low potential states, which causes repeated reduction and oxidation of the catalysts in the fuel cell electrodes, especially platinum, which is frequently used on the cathode side of the MEA. This results in repeated dissolution and precipitation of platinum, and a process known as "Ostwald ripening," in which individual catalyst particles agglomerate, reducing the catalyst's surface area during operation and reducing power output.
[0004] (J. Electrochem. Soc. 2007, 154(1), B96-B105) reported the contamination of platinum-based carbon-supported (Pt / C-) catalysts with halides and the resulting loss of catalytic activity. It was also noted that adsorbed halides promote the (electro)chemical dissolution of Pt or PtO.
[0005] Halogenated intermediates in the production of perfluorinated polymers, which are used, for example, as ionomers in fuel cell membranes and fuel cell electrodes, are described, for example, in DE 10 2018 002 337 A1, as a source of halide impurities. The effect of increased platinum dissolution by chloride or bromide is described in DE 10 2018 002 337 A1 and in Electrochimica Acta 52 (2007): 7444-7552 cited therein, whereby even very low percentages of about 1 ppm are described as being negative. A chloride concentration of 4 ppm should already lead to a voltage loss of 50 mV. Furthermore, chloride increases the production of H2O2 and causes chemical degradation, which leads to membrane thinning and the formation of holes. DE 10 2018 002 337 A1 therefore provides a method for improving the long-term stability of MEAs, which reduces the amount of halide ions by adding silver carbonate, forming silver halide, which is then decomposed by irradiation with light, releasing the halogens. Summary of the Invention [Problem to be solved by the invention]
[0006] Based on the prior art cited above, it is an object of the present invention to provide a fuel cell electrode, a catalyst coated membrane, and also a fuel cell with improved long-term stability, which does not lead to a decrease in performance when used as intended. Furthermore, it is an object of the present invention to provide a method for producing a permanently stable fuel cell electrode and a permanently stable catalyst coated membrane, as well as a fuel cell, which is simple and cheap to implement, does not lead to a loss of performance, and improves the permanent stability of the fuel cell electrode and therefore also the catalyst coated membrane and the fuel cell. [Means for solving the problem]
[0007] For this purpose, the fuel cell electrode according to the invention comprises a metal-containing catalyst and a proton-conducting ionomer. The fuel cell electrode can be designed as a cathode or an anode. If necessary, the fuel cell electrode can also comprise a corresponding metal-containing catalyst, i.e., in the case of the cathode, an oxygen-reducing metal-containing catalyst (which corresponds to the first metal-containing catalyst in the catalyst-coated membrane of the invention), and in the case of the anode, a hydrogen-oxidizing metal-containing catalyst (which corresponds to the second metal-containing catalyst in the catalyst-coated membrane of the invention). The proton-conducting ionomers of the anode and the cathode can be the same or different.
[0008] The fuel cell electrode is characterized by a halide concentration of 50 to 1000 ppm, based on the total mass of the fuel cell electrode. This means that halide ions, for example in the form of a halide-containing solution, are actively added to the fuel cell electrode. The amount of halides already contained in the individual components of the fuel cell electrode counts towards the halide concentration of 50 to 1000 ppm. These can be, for example, halide ions introduced by precursors or ionomers of metal-containing catalysts. However, the amount of halide concentration already contained in the individual components of the fuel cell electrode is negligibly small, in particular not more than 20 ppm, in particular not more than 10 ppm. Thus, to achieve a halide concentration of 50 to 1000 ppm, at least one halide is actively added to the fuel cell electrode. According to the present invention, the halide concentration in the fuel cell electrode means the halide concentration before the fuel cell electrode is used as intended.
[0009] The halide concentration can be adjusted by adding one halide or a combination of two or more halides. The halide is not particularly limited and is introduced into the fuel cell electrode in particular as a dissolved salt. The halide in the fuel cell electrode is determined using ion chromatography. The halide can be differentiated by its retention time using ion chromatography (retention time: e.g. F: 6.9 min, Cl: 10.4 min, Br: 15.9 min). 1.9 liters of aqueous sodium carbonate solution with a concentration of 3.2 mmol / L and 1.0 liters of aqueous sodium bicarbonate solution with a concentration of 1.0 mmol / L mixed with 0.1 liters of acetone thyryl are used as the solvent, totaling 2.0 liters of solvent. The measurement is carried out using a Metrohm 690 IC (Deutsche METROHM GmbH & Co.KG, Germany). The column used is a Metrosep A Supp7-250 / 4.0 mm model (Deutsche METROHM GmbH & Co.KG, Germany). The column temperature was set at 40°C and the flow rate was 0.7 ml min -1 In ion chromatography, free ions can be measured depending on the sample preparation, i.e. fluorine that is covalently bound, for example in polymers, is not detected. For this purpose, the halides are extracted, for example with water. If the concentration of halides is otherwise to be measured in one of the components of the fuel cell electrode, the sample can also be ashed and measured. For chloride ions, the sample can be prepared using the so-called oxygen pressure digestion method. In this method, the sample is burned under pressure with the addition of oxygen in a closed system, and the covalently bound analytes in the sample are liberated and analyzed using ion chromatography. Since chloride ions are usually not contained in a bound state in any component, the chloride ion concentration of the free chloride ions also corresponds to the chloride ion concentration of the entire fuel cell electrode.
[0010] When the fuel cell electrode is used as intended in a fuel cell, in particular when used together with a second fuel cell electrode and a membrane disposed between the two fuel cell electrodes, it is preferred that only the fuel cell electrode according to the invention comprises an addition of a halide, the halide concentration of this fuel cell electrode being in the range 150-6000 ppm, and that no further halide is added to the second fuel cell electrode and membrane.
[0011] Surprisingly, halide concentrations between 150 and 6000 ppm based on the total mass of the fuel cell electrode have been shown to improve the long-term stability of the fuel cell electrode, thus preventing degradation of the metal-containing catalyst. The halide concentrations do not degrade the performance of the fuel cell electrode when used as intended.
[0012] The dependent claims relate to advantageous further developments and embodiments of the invention.
[0013] Considering the balance between the long-term stability and performance of the fuel cell electrode, the fuel cell electrode preferably has a halide concentration of 300 to 3000 ppm based on the total mass of the fuel cell electrode.
[0014] As disclosed above, the halide used is virtually unlimited. Advantageously, the halide is selected from the group consisting of fluorides, chlorides, bromides, iodides and mixtures thereof, preferably chlorides due to their very good availability and processability, and due to their low adverse effects.
[0015] According to an advantageous further development, the metal-containing catalyst comprises a precious metal, or a mixture or alloy of two or more precious metals, or a precious-non-precious metal alloy, the non-precious metal alloy being particularly suitable for fuel cell electrodes designed as cathodes, and the pure precious metal catalyst being particularly suitable for fuel cell electrodes designed as anodes.
[0016] It is preferred here if the precious metal-non-precious metal alloy consists of a platinum alloy and / or if the precious metal of the metal-containing catalyst consists of platinum and / or palladium.
[0017] Since degradation of metal-containing catalysts due to potential cycling is particularly pronounced on the cathode side of a fuel cell, the fuel cell electrode according to the invention is preferably designed as a cathode.
[0018] Further according to the invention, a catalyst coated membrane is also described, which comprises a fuel cell electrode as described above. By using the fuel cell electrode according to the invention, the catalyst coated membrane according to the invention (hereinafter referred to as CCM) is also characterized by very high long-term stability with consistently good performance. Thus, the CCM according to the invention has the same advantageous effects as described above for the fuel cell electrode according to the invention. These advantageous effects are due to the halide concentration of 150-6000 ppm in the fuel cell electrode used.
[0019] Furthermore, according to the present invention, a method for producing the fuel cell electrode disclosed above is also described. In a step of the method according to the present invention, a halide concentration is added to the fuel cell electrode so that the halide concentration of the fuel cell electrode is 150-6000 ppm, preferably 300-3000 ppm, based on the total mass of the fuel cell electrode. Addition of a halide concentration here means that the halide is added, especially in the form of a soluble salt, and is not already introduced together with the other fuel cell electrode elements, i.e. in particular the ionomer and the metal-containing catalyst. The halide or halides are added separately and therefore independently from the other fuel cell electrode elements.
[0020] By adding one or more halides, fuel cells can be produced that have high long-term stability without any loss in performance, and this process can be achieved without significant technical expenditure and time.
[0021] According to an advantageous further development, the addition of halide concentration is carried out so that the fuel cell electrode is manufactured with a solution that contains at least one halide.By manufacturing with a solution that contains a halide, it is possible to achieve a very uniform distribution of the halide in the fuel cell electrode, so that the fuel cell electrode is equally well protected from deterioration in each catalytically active area, and therefore, during the intended use, no performance deterioration is recorded.
[0022] The fuel cell electrode can be prepared as an anode or a cathode. The anode or cathode is prepared, in particular, from an anode dispersion or a cathode dispersion, in which the halide-containing compound is present in an amount of 100 parts by weight of halide in the anode dispersion. A is added to the anode dispersion liquid or the cathode dispersion liquid so as to satisfy the following formula:
[0023]
number
[0024] In the above formula, A is 150 to 6000 ppm, preferably 300 to 3000 ppm, and B is the solid content of the negative electrode dispersion liquid.
[0025] Alternatively, the parts by weight of halide in the cathode dispersion F K satisfies the following formula:
[0026]
number
[0027] Here, A is 150 to 6000 ppm, preferably 300 to 3000 ppm, and B is the solid content of the cathode dispersion.
[0028] As disclosed above, the halide is preferably selected from the group consisting of fluoride, chloride, bromide, iodide and mixtures thereof, preferably chloride due to its very good availability and low adverse effects.
[0029] According to an advantageous further development, the cation of the halide-containing compound used to generate the required halide concentration is selected from the group of protons, alkali metals, alkaline earth metals, ammonium ions or cationic organic compounds. Particularly preferred cations are Na + and K. + It is.
[0030] To further simplify the method, a fuel cell electrode is produced by preparing a fuel cell electrode dispersion in which the metal-containing catalyst and the proton-conducting ionomer are dispersed, and a halide-containing compound is added to the fuel cell electrode dispersion before, during or after the dispersion, the addition of the halide-containing compound being carried out in conjunction with further dispersion, particularly to achieve a uniform distribution of the halide or halide.
[0031] The method according to the invention can be used to manufacture a fuel cell electrode according to the invention.Therefore, a fuel cell electrode manufactured according to the above-mentioned method is also described, which is characterized by a high long-term stability and at the same time no loss of performance.
[0032] Also described in accordance with the present invention is a catalyst coated membrane comprising a cathode, an anode, and a proton conducting membrane therebetween, wherein the cathode comprises a first metal-containing catalyst and a proton conducting ionomer, the anode comprises a second metal-containing catalyst and a proton conducting ionomer, and the membrane comprises the proton conducting ionomer.
[0033] According to the invention, a catalyst coated membrane refers to a configuration in which the anode and cathode surround the membrane on both sides and the membrane is placed between the cathode and the anode. The anode and the cathode can be coated directly on the membrane to form a composite. In this case, it is specifically called a CCM, i.e. a "catalyst coated membrane". Furthermore, a catalyst coated membrane refers to a configuration for use in a fuel cell, in which the anode and the cathode are placed on the two sides of the membrane, specifically stacked. In both cases, the two exposed sides of the anode and the cathode can be provided with gas diffusion layers (GDLs). If gas diffusion layers are provided, the overall configuration is also called a membrane electrode assembly (MEA). According to the invention, the halide concentration in the case of a catalyst coated membrane refers to the configuration designed as above without GDLs.
[0034] The catalyst coated membrane according to the invention has a halide concentration of 50-1000 ppm, based on the total mass of the catalyst coated membrane. The halide concentration is therefore the sum of the individual halide concentrations of the anode, cathode and membrane, meaning the total mass of these components. The halide concentration of 50-1000 ppm is not essentially introduced by the metal-containing catalyst and ionomer, but is explicitly added until the desired halide concentration is reached. The halide concentration in the catalyst coated membrane is determined by ion chromatography, as already described for the fuel cell electrodes. Depending on the sample preparation method selected or the choice of the halides to be measured, only free halides and halides bound non-covalently or in other ways (e.g. complexes) are detected in the catalyst coated membrane. Fluorides present in the ionomer (such as when fluorinated ionomers are used) or bound to the membrane are not detected by water extraction and subsequent measurement using ion chromatography.
[0035] The halide is preferably present mainly at the cathode, since the cathode is particularly susceptible to catalyst degradation. However, the desired halide concentration can also be adjusted at the anode or in the membrane, since the halide ions can partially migrate through the layer of the catalyst-coated membrane. When the catalyst-coated membrane is used as intended, the effect on the long-term stability of the catalyst-coated membrane is that the halide is uniformly distributed in the layer and therefore has a uniform stabilizing effect without reducing the performance of the catalyst-coated membrane.
[0036] The essential halide concentration of 50-1000 ppm for the present invention, relative to the total mass of the catalyst coated membrane, is present both in unused (i.e. freshly manufactured) catalyst coated membranes and in catalyst coated membranes during or after intended use. This is because the halide can be added to the anode and / or cathode and / or membrane in the desired concentration, so that a total halide concentration of 50-1000 ppm is achieved, based on the total mass of the catalyst coated membrane. Even if the halide subsequently migrates from the original component to other components of the catalyst coated membrane (e.g. from the cathode to the anode, or from the anode to the cathode, or from the cathode to the membrane and / or the anode, or from the anode to the membrane and / or the cathode), for example during the intended use, the halide concentration based on the total mass of the catalyst coated membrane always remains the same, i.e. 50-1000 ppm according to the present invention.
[0037] This is consistent with the fuel cell electrodes according to the invention described above. When a fuel cell electrode according to the invention, having a halide concentration of 50-1000 ppm, is used with a catalyst coated membrane according to the invention, one or more halides may also be added to the other fuel cell electrodes and / or membranes such that the total halide concentration of the catalyst coated membrane is 50 ppm-1000 ppm, based on the total weight of the catalyst coated membrane, so long as the halide concentration in the fuel cell electrode used is at least 50 ppm but less than 1000 ppm.
[0038] Also, a fuel cell electrode according to the invention having a halide concentration of less than 1000 ppm can be combined with a fuel cell electrode not according to the invention, for example having a halide concentration of less than 50 ppm based on the total mass of the fuel cell electrode, provided that in the catalyst coated membrane according to the invention, the halide concentration based on the total mass of the catalyst coated membrane according to the invention is in the range of 50 to 1000 ppm.
[0039] It is also possible to form a catalyst coated membrane according to the invention in combination with two fuel cell electrodes not according to the invention (e.g., both of which each have a halide concentration of less than 50 ppm, based on the total mass of each of the corresponding fuel cell electrodes), resulting in a halide concentration of 50-1000 ppm, based on the total mass of the catalyst coated membrane.
[0040] However, preferably the desired halide concentration of 50-1000 ppm based on the total mass of the catalyst coated membrane is introduced into the fuel cell, particularly via the cathode, so that the fuel cell halide concentration relative to the total mass of the fuel cell in the fuel cell is reflected in the catalyst coated membrane halide concentration relative to the total mass of the catalyst coated membrane. However, the distribution of halide in the individual layers of the catalyst coated membrane may vary when the membrane is used as intended, without changing the halide concentration relative to the total mass of the catalyst coated membrane according to the invention.
[0041] To improve the balance of effects of improving long-term stability while maintaining high performance, the halide concentration in the catalyst coated membrane is preferably 50-500 ppm based on the total mass of the catalyst coated membrane.
[0042] As already disclosed above, the halide used is essentially not limited. Advantageously, however, the halide is selected from the group consisting of fluorides, chlorides, bromides, iodides and mixtures thereof, preferably chlorides due to their very good availability and low adverse effects.
[0043] According to an advantageous further development, the first and second metal-containing catalysts comprise a precious metal, or a mixture or alloy of two or more precious metals, or a precious metal-non-precious metal alloy.
[0044] It is preferred herein if the precious metal-non-precious metal alloy comprises a platinum alloy and / or if the precious metal of the metal-containing catalyst comprises platinum and / or palladium.
[0045] According to a further preferred embodiment, the anode of the catalyst coated membrane comprises a halide of parts by weight F according to the formula A has.
[0046]
number
[0047] Here, A is 50 to 1000 ppm, preferably 50 to 500 ppm, and M CCM is the areal weight of the catalyst-coated membrane, and M CLA is the area weight of the anode.
[0048] More preferably, the cathode of the catalyst coated membrane comprises at least one part by weight of halide F according to the formula: K has.
[0049]
number
[0050] Here, A is 50 to 1000 ppm, preferably 50 to 500 ppm, and M CCM is the areal weight of the catalyst-coated membrane, and M CLK is the area weight of the cathode.
[0051] The above formula will be explained with reference to the following examples, but the examples are for illustrative purposes only and are not intended to limit the present invention. For example, depending on the type, the film thickness is 8 to 20 μm, and as a result, the area weight (M CCM ) is 1.6-4mg / cm 2 It becomes.
[0052] For a membrane with a thickness of 12 μm, the membrane area weight M CCM is 2.4 mg / cm 2 It becomes.
[0053] Electrode area weight (M CLA or M CLK ) depends on several factors. Catalyst loading (e.g. platinum and / or palladium) The platinum content of the catalyst (typically 20wt%-60wt%) Ionomer content (specifically the ionomer to carbon ratio I:C)
[0054] <Example> 0.1mg(Pt) / cm 2 , 20wt%Pt / C, and l:C 0.8:1 anode Area weight (M CLA )=0.82mg / cm 2 0.5mg(PtCo) / cm 2 , 50%Pt / C, and l:C 1:1 cathodes Area weight (M CLK )=1.5mg / cm 2 Total area weight (M CCM )=4.72mg / cm 2 Anode factor (F A )=5.76→F A =288~5760ppm Cathode factor (F K )=3.15→F K =157~3150ppm
[0055] Furthermore, the present invention also describes a fuel cell having very good long-term stability and consistently good performance. The fuel cell according to the present invention is characterized in that it comprises a catalyst-coated membrane as described above, so that the fuel cell also has the above-mentioned advantageous effects.
[0056] The advantages, benefits and further developments explained in each case for the fuel cell electrode according to the invention, the catalyst coated membrane according to the invention and the fuel cell according to the invention apply mutually in each case.
[0057] Further according to the present invention, a method for preparing the catalyst coated membrane as disclosed above is also described, in which a halide concentration is added to the cathode and / or anode and / or proton conducting membrane such that the halide concentration of the catalyst coated membrane is 50-1000 ppm, preferably 50-500 ppm, based on the total mass of the catalyst coated membrane. Thus, the halide concentration is composed of the individual halide concentrations of the anode, cathode and membrane, and is related to the total mass of these elements / components.
[0058] The desired halide concentration is obtained by adding one or more halides, and thus is not already provided by the use of a halide-containing catalyst precursor and a halide-containing ionomer, but is specifically added to each element of the catalyst layer membrane being produced.
[0059] The halide concentration is 50-1000 ppm, preferably 50-500 ppm, which improves the long-term stability of the catalyst coated membrane without compromising performance. The process is easy to carry out without high technical effort and is therefore very efficient.
[0060] The method according to the invention for producing a catalyst coated membrane is suitable for producing a catalyst coated membrane according to the invention.
[0061] In order to achieve a particularly uniform halide ion concentration in the catalyst-coated membrane, the catalyst-coated membrane is prepared using a solution containing at least one halide. The preparation using a halide-containing solution can be carried out for one, several or even all layers of the catalyst-coated membrane, provided that the desired halide concentration based on the total weight of the catalyst-coated membrane is achieved. The preparation of the catalyst-coated membrane using a halide solution is technically particularly easy to carry out, does not require significant technical efforts and allows a particularly uniform distribution of the halide or halides in the corresponding layers.
[0062] According to an advantageous further development, the anode is prepared from an anode dispersion and the cathode is prepared from a cathode dispersion, the anode dispersion and / or the cathode dispersion are added with a halide-containing compound, and the parts by weight of halide in the anode dispersion F A satisfies the following equation:
[0063]
number
[0064] Here, A is 50 to 1000 ppm, preferably 50 to 500 ppm, B is the solid content of the anode dispersion, and M CCM is the areal weight of the catalyst-coated membrane, and M CLA is the area weight of the anode.
[0065] Alternatively or additionally, the parts by weight of halide in the cathode dispersion F K satisfies the following formula:
[0066]
number
[0067] Here, A is 50 to 1000 ppm, preferably 50 to 500 ppm, B is the solid content of the cathode dispersion, and M CCM is the areal weight of the catalyst-coated membrane, and M CLKis the area weight of the cathode.
[0068] The anode dispersion and the cathode dispersion can have different halide weight ratios.
[0069] The halide is not substantially limited and can be selected from fluoride, chloride, bromide or iodide, with chloride being particularly preferred as the halide.
[0070] For better solubility, the cation of the halide-containing compound used to adjust the halide concentration is selected from the group of protons, alkali metals, alkaline earth metals, ammonium ions or cationic organic compounds. Particularly preferred cations are Na + and K. + It is.
[0071] To further simplify the process, the anode and cathode dispersions are coated onto the membrane either directly or via a decal substrate.
[0072] According to a further advantageous development, to produce a cathode, a cathode dispersion is prepared, in which a first metal-containing catalyst and a proton-conducting ionomer are dispersed. Even more advantageously, to produce an anode, an anode dispersion is prepared, in which a second metal-containing catalyst and a proton-conducting ionomer are dispersed. Furthermore, a halide-containing compound is added to the cathode dispersion and / or the anode dispersion before, during or after the dispersion, so that the desired halide ion concentration can be set.
[0073] Dispersion can be carried out using typical technical aids, is technically simple, and can be achieved quickly since the solubility of the halide-containing compounds is usually very good.
[0074] In the following, exemplary process steps for producing a catalyst coated membrane according to the present invention are given. Further process steps may also be provided.
[0075] <Preparation of catalyst dispersion> The catalyst dispersion (also called fuel cell electrode dispersion) is prepared by mixing the metal-containing catalyst in water, solvent and ionomer dispersion. The ionomer used in the catalyst layer according to the present invention is not specifically limited, and fully fluorinated ionomer (PFSA), partially fluorinated ionomer or hydrocarbon-based (non-fluorinated) ionomer can be used. The catalyst dispersion is ground in a ball mill (grinding media: ZrO2 balls) for about 120 minutes. The catalyst layer is produced by applying the catalyst dispersion onto an inert substrate, a so-called decal, and drying it.
[0076] Alternatively, for example, ultrasonics or the use of various grinding media mills can be used to prepare the dispersion, including, for example, ball mills, agitator bead mills, agitator mills, attritors, and certain roller mills.
[0077] To prepare a catalyst dispersion according to the present invention with a lower chloride concentration, the required amount of 5% by weight of aqueous sodium chloride solution is added to the catalyst ink after the dispersion step and then stirred on a magnetic stirrer for at least 2 hours. To adjust to a higher chloride concentration, the required amount of 20% by weight of aqueous sodium chloride solution is added to the catalyst ink after the dispersion step and then stirred on a magnetic stirrer for at least 2 hours.
[0078] Preparation of the catalyst coated membrane according to the present invention The cathode and anode layers, consisting of the correspondingly produced anode and cathode dispersions, can be coated on an inert film and dried. For coating, common techniques such as slot nozzles, doctor blades, spiral applicators, screen printing or spray devices can be used. The layers are then transferred to the membrane in a lamination step (the so-called decal step), the lamination temperature is usually 150-190 ° C and the pressure is 1-3 MPa. Lamination can be carried out, for example, in a press or continuously between a pair of rollers. The lamination time in a press is about 1 minute in discontinuous operation and a few seconds in continuous operation.
[0079] Alternatively, the cathode and / or anode can be applied directly to the membrane and dried (direct printing method).
[0080] As a further alternative, the cathode and / or anode can be deposited on a gas diffusion layer (GDL) and dried to obtain a so-called gas diffusion electrode (GDE), which is then contacted with the membrane to obtain a membrane electrode assembly (GDE process).
[0081] As a further alternative, a first electrode can be applied to the membrane (via a decal process or even via a direct printing process) and a second electrode applied to the GDL.
[0082] For the purposes of this invention, different methods of manufacturing the membrane electrode assembly are considered to be of equal scope.
[0083] The method according to the invention for producing a catalyst coated membrane can be used to produce a catalyst coated membrane according to the invention. Thus, a catalyst coated membrane produced according to the above method is also described, which is characterized by a high long-term stability and at the same time no loss of performance.
[0084] <Example> In the following, the invention will be explained in more detail with reference to examples and figures. [Brief description of the drawings]
[0085] [Figure 1] FIG. 1 is a cross-sectional schematic diagram of a catalyst coated membrane according to an embodiment. [Diagram 2] FIG. 2 shows the voltage loss of the example after 30,000 potential cycles between 0.6 and 0.95V. [Diagram 3] FIG. 3 shows the mass activity loss of an example after 30,000 potential cycles between 0.6 and 0.95 V. [Figure 4] Figure 4 shows the EPSA loss (catalyst surface) after 30,000 potential cycles between 0.6 and 0.95 V. [Diagram 5] FIG. 5 shows the long-term chemical stability of a sample with no chloride (solid line) and a sample with measured chloride levels of 220 ppm (dashed line). [Figure 6] FIG. 6 shows the cell voltage of the sample at 0.8 A / cm2 at the start of the measurement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0086] In the figures, only the essential elements and components of the present invention are shown, all other elements and components are omitted for clarity.
[0087] FIG. 1 is a schematic cross-sectional view of a catalyst coated membrane 1 according to one embodiment. The catalyst coated membrane 1 has a cathode 2, an anode 3 and a proton conducting membrane 4 located therebetween, the cathode 2 comprising a first metal-containing catalyst 5 and a proton conducting ionomer 6, the anode 3 comprising a second metal-containing catalyst 7 and a proton conducting ionomer 8, and the membrane 4 comprising a proton conducting ionomer. The catalyst coated membrane 1 has a halide concentration of 50 to 1000 ppm, based on the total mass of the catalyst coated membrane 1. The halide 9 is in particular a chloride, which is here explicitly arranged at the cathode 2. Particularly preferably, the halide 9 is introduced to the cathode 3 in the form of a NaCl solution.
[0088] Depending on the halide concentration, the catalyst coated membrane 1 is characterized by very good long-term stability without any significant degradation of performance.
[0089] <Potential cycle test> The potential cycling test constitutes an accelerated stability test that simulates the voltage curve of the cathode during dynamic operation of the fuel cell, ie under normal operating conditions when power is extracted from the fuel cell.
[0090] The potential cycle test was conducted as follows in accordance with the recommendations of the U.S. Department of Energy (DOE).
[0091] Single Cell T Zelle The temperature of the anode was 80°C, and the temperature of the humidifier was 80°C at the anode and 80°C at the cathode. Hydrogen was supplied to the anode and nitrogen to the cathode at normal pressure. A square wave voltage was applied to the cell, alternating between a voltage of 0.6 V for 3 seconds and a voltage of 0.95 V for 3 seconds. This cycle was repeated 30,000 times.
[0092] <Long-term chemical stability test> The chemical long-term stability test is an accelerated stability test that tests the crossing of the catalyst coated membrane by hydrogen while operating under open circuit voltage.
[0093] Long-term chemical stability studies were performed in accordance with U.S. Department of Energy (DOE) recommendations as follows:
[0094] T Zelle The cell temperature was set at 90°C and humidification at 30% RH. Hydrogen was supplied to the anode and air to the cathode at 1.5 bar. No current was passed and the cell was under open circuit voltage. Hydrogen crossover was measured at regular intervals.
[0095] Ion Chromatography for Determination of Halide Content Sample preparation prior to the determination of halide, especially chloride, content using ion chromatography was performed under oxygen pressure digestion, where the sample material was combusted under pressure with the addition of oxygen in a closed system.
[0096] The halides in the fuel cell electrodes were measured using ion chromatography. The halides can be distinguished by their retention times using ion chromatography (retention times: e.g., F: 6.9 min, Cl: 10.4 min, Br: 15.9 min). In this case, a mixture of 1.9 liters of a 3.2 mmol / L aqueous sodium carbonate solution and a 1.0 mmol / L aqueous sodium bicarbonate solution, and 0.1 liters of acetonitrile was used as the eluent, resulting in a total of 2.0 liters of eluent. The measurements were performed using a Metrohm 690 IC (Deutsche METROHM GmbH & Co. KG, Germany). As a column, a Metrosep A Supp7-250 / 4.0 mm (Deutsche METROHM GmbH & Co. KG, Germany) was used. The column temperature was set to 40°C, and the flow rate was 0.7 mL min -1 It was decided.
[0097] <Example 1> A catalyst-coated membrane was prepared as described above. The cathode prepared according to Example 1 contained a pure platinum catalyst supported on carbon (50 wt. % platinum, 50 wt. % carbon) as the catalyst. The precious metal areal weight of the metal-containing catalyst was 0.4 mgpt / cm. 2 The cathode further contained an ionomer (Aquivion™ D79-25BS; Solvay Specialty Polymers, Italy) with an equivalent weight (EW) of 790 g / mol. The mass ratio of ionomer to carbon-containing support material was 0.8:1.
[0098] The cathode according to Example 1, in accordance with the present invention, further contained sodium chloride with a chloride concentration of 1370-1500 ppm as determined by ion chromatography as described above.
[0099] The anode prepared according to Example 1 contains a pure platinum catalyst supported on carbon (20 wt. % platinum, 80 wt. % carbon) as a catalyst. The precious metal area weight of the metal-containing catalyst is 0.1 mgpt / cm. 2 The anode further contained an ionomer (Aquivion™ D79-25BS; Solvay Specialty Polymers, Italy) with an equivalent weight (EW) of 790 g / mol. The mass ratio of ionomer to carbon-containing support material was 0.8:1.
[0100] The MEAs produced according to Example 1 were fabricated using the decal process described above. The anode and cathode were each applied to a glass fiber reinforced PTFE substrate using a spiral applicator. The wet film thickness was selected to achieve the target loading. Each catalyst dispersion was then dried in an oven at 100°C for 5 minutes. Lamination (decal transfer) of the anode and cathode with the membrane (perfluorinated enhanced sulfonic acid membrane, 15 μm thick) was performed with a band laminator at a temperature of 180°C and a pressure of 1 MPa for 1 minute.
[0101] Thus, the chloride content of the catalyst coated membrane was 310-340 ppm.
[0102] <Examples 2 and 3, Comparative Examples 1 to 3> Examples 2 and 3 and Comparative Examples 1-3 were prepared similarly to Example 1, but with the compositions shown in Table 1 below.
[0103] Table 1 below shows an overview of the tests carried out and their respective test results. It shows the examples and comparative examples, their chloride contents, and the losses due to potential cycling tests from 0.6 to 0.95 V (values calculated by subtracting the values at the end of the tests from the values at the start of the tests).
[0104] [Table 1]
[0105] As non-graphitized carbon, for example, carbon under the trademark Vulcan from Cabot Corporation can be used. Here, "EPSA" means effective platinum surface area. The term "geo" means the geometrically active surface area of the catalyst coated membrane. Thus, EPSA is the surface area of platinum per area of the catalyst coated membrane [cm 2 (Pt)] is shown.
[0106] As shown in FIGS. 1 to 3, the examples according to the present invention have a much lower voltage loss after 30,000 potential cycles between 0.6 and 0.95 V (see FIG. 2), a lower mass activity loss after 30,000 potential cycles between 0.6 and 0.95 V (see FIG. 3), and a lower EPSA loss (effective platinum surface area - platinum surface area to electrode area; i.e., EPSA is the surface area of platinum [cm 2 (Pt)] is low (see Figure 4).
[0107] The chlorides in the ppm range used result in reduced voltage loss, reduced mass activity loss, and reduced EPSA loss. Furthermore, no negative effects on chemical long-term stability were observed, which can be seen especially in Figure 5. No effects were observed with increasing H2O2 concentrations.
[0108] FIG. 6 shows that the chloride content does not significantly affect the cell voltage, i.e., there is no degradation of the cell voltage.
[0109] In addition to the above description of the invention, explicit reference is made to the drawings of the invention in FIGS. 1 to 6 for a supplementary disclosure thereof. [Explanation of symbols]
[0110] 1 Catalyst coated membrane 2 Cathode 3 Anode 4 membrane 5 First metal-containing catalyst 6. Proton Conductive Ionomers 7 Second metal-containing catalyst 8. Proton Conductive Ionomers 9. Halides [Prior art documents] [Patent documents]
[0111] [Patent Document 1] German Patent Application Publication No. 102018002337 [Non-patent literature]
[0112] [Non-Patent Document 1] Guilminot et al., J. Electrochem. Soc. 2007, 154(1), B96-B105
Claims
1. A fuel cell electrode (2, 3) comprising a metal-containing catalyst (5, 7) and a proton-conducting ionomer (6, 8), characterized in that the fuel cell electrode (2, 3) has a halide concentration of 150 to 6000 ppm, based on the total mass of the fuel cell electrode (2, 3).
2. the fuel cell electrodes (2, 3) have a halide concentration of 300 to 3000 ppm, based on the total mass of the fuel cell electrodes (2, 3); and / or 2. The fuel cell electrode (2, 3) according to claim 1, characterized in that the halide is selected from the group consisting of fluoride, chloride, bromide, iodide and mixtures thereof, preferably chloride.
3. the metal-containing catalyst (5, 7) comprises a precious metal, a mixture or alloy of two or more precious metals, or a precious metal-non-precious metal alloy; the precious metal-non-precious metal alloy comprises, in particular, a platinum alloy; and / or 3. Fuel cell electrode (2, 3) according to claim 1 or 2, characterized in that the noble metal of the metal-containing catalyst (5, 7) comprises in particular platinum and / or palladium.
4. A fuel cell electrode (2, 3) according to any one of claims 1 to 3 configured as a cathode (2).
5. A catalyst coated membrane (1) comprising a fuel cell electrode (2, 3) according to any one of claims 1 to 4.
6. A method for manufacturing a fuel cell electrode (2,3) according to any one of claims 1 to 4, characterized in that a halide concentration is added to the fuel cell electrode (2,3) such that the halide concentration of the fuel cell electrode (2,3) is 150 to 6000 ppm, preferably 300 to 3000 ppm, based on the total mass of the fuel cell electrode (2,3).
7. 7. The method according to claim 6, characterized in that the fuel cell electrodes (2, 3) are manufactured using a solution containing at least one halide.
8. said fuel cell electrodes (2, 3) are produced as an anode (3) from an anode dispersion or as a cathode (2) from a cathode dispersion, a halide-containing compound being added to said anode dispersion or said cathode dispersion, Part by weight F of the halide in the anode dispersion A satisfies the following formula, [0070] where A is between 150 and 6000 ppm, preferably between 300 and 3000 ppm, and B is the solids content of the anode dispersion; or Part by weight F of the halide in the cathode dispersion K satisfies the following formula, [0080] wherein A is 150-6000 ppm, preferably 300-3000 ppm, and B is the solids content of the cathode dispersion; the anode dispersion and the cathode dispersion may have different parts by weight of halide; and / or the cation of the halide-containing compound is selected from the group of a proton, an alkali metal, an alkaline earth metal, an ammonium ion, or a cationic organic compound; and / or 8. The method according to claim 6 or 7, characterized in that for producing the fuel cell electrodes (2, 3), a fuel cell electrode dispersion is prepared in which a metal-containing catalyst (5, 7) and a proton-conducting ionomer (6, 8) are dispersed, and a halide-containing compound is added to the fuel cell electrode dispersion before, during or after the dispersion.
9. A catalyst coated membrane comprising a cathode (2), an anode (3) and a proton conducting membrane (4) disposed therebetween, a. the cathode (2) comprises a first metal-containing catalyst (5) and a proton-conducting ionomer (6); b. the anode (3) comprises a second metal-containing catalyst (7) and a proton-conducting ionomer (8); c. the membrane (4) comprises a proton-conducting ionomer; The catalyst coated membrane (1) has a halide concentration of 50 to 1000 ppm, based on the total mass of the catalyst coated membrane (1).
10. the catalyst coated membrane (1) has a halide concentration of 50 to 500 ppm, based on the total mass of the catalyst coated membrane (1); and / or the halide is selected from the group consisting of fluoride, chloride, bromide, iodide, and mixtures thereof, preferably chloride; and / or the first metal-containing catalyst (5) and the second metal-containing catalyst (7) comprise a precious metal, or a mixture or alloy of two or more precious metals, or a precious metal-non-precious metal alloy; the precious metal-non-precious metal alloy comprises, in particular, a platinum alloy; and / or 10. Catalyst coated membrane (1) according to claim 9, characterized in that the precious metal of the second metal-containing catalyst (7) comprises in particular platinum and / or palladium.
11. The anode (3) contains F parts by weight of a halide corresponding to the formula A having [0090] Here, A is 50 to 1000 ppm, preferably 50 to 500 ppm, and M CCM is the areal weight of the catalyst coated membrane (1), M CLA is the areal weight of the anode (3), or The cathode (2) contains F parts by weight of a halide corresponding to the following formula: K having [0089] Here, A is 50 to 1000 ppm, preferably 50 to 500 ppm, and M CCM is the areal weight of the catalyst coated membrane (1), M CLK Catalyst coated membrane (1) according to claim 9 or 10, characterized in that x is the areal weight of the cathode (2).
12. A fuel cell comprising a catalyst coated membrane according to any one of claims 9 to 11.
13. A method for producing a catalyst coated membrane (1) according to any one of claims 9 to 11, comprising the steps of:
1. A method for producing a catalyst coated membrane (1), characterized in that a halide concentration is added to the cathode (2) and / or the anode (3) and / or the proton conducting membrane (4) such that the halide concentration of the catalyst coated membrane (1) is 50-1000 ppm, preferably 50-500 ppm, based on the total mass of the catalyst coated membrane (1).
14. the catalyst coated membrane (1) is produced using a solution containing at least one halide, and / or The anode (3) is produced from an anode dispersion and the cathode (2) is produced from a cathode dispersion; a halide-containing compound is added to the anode dispersion and / or the cathode dispersion; Part by weight F of the halide in the anode dispersion A satisfies the following formula, ##EQU00011## where A is 50 to 1000 ppm, preferably 50 to 500 ppm, B is the solids content of the anode dispersion, and M CCM is the areal weight of the catalyst coated membrane (1), M CLA is the areal weight of the anode (3), and / or Part by weight F of the halide in the cathode dispersion K satisfies the following formula, ##EQU00012## where A is 50-1000 ppm, preferably 50-500 ppm, B is the solids content of the cathode dispersion, and M CCM is the areal weight of the catalyst coated membrane (1), M CLK is the area weight of the cathode (2), the anode dispersion and the cathode dispersion may have different parts by weight of halide; and / or the cation of the halide-containing compound is selected from the group of a proton, an alkali metal, an alkaline earth metal, an ammonium ion, or a cationic organic compound; and / or The anode dispersion and the cathode dispersion are coated directly onto the membrane (4) or coated onto the membrane (4) via a decal substrate; and / or 14. The method according to claim 13, characterized in that for producing the cathode (2), a cathode dispersion is prepared, in which a first metal-containing catalyst (5) and a proton-conducting ionomer (8) are dispersed, and for producing the anode (3), an anode dispersion is prepared, in which a second metal-containing catalyst (7) and a proton-conducting ionomer (8) are dispersed, and a halide-containing compound is added to the cathode dispersion and / or to the anode dispersion before, during or after the dispersion.
Citation Information
Patent Citations
Method for manufacturing electrode catalyst, electrode catalyst, composition for gas diffusion electrode formation, gas diffusion electrode, membrane-electrode assembly (MEA) and fuel battery stack
JP2015195208A
Method for manufacturing electrode catalyst, electrode catalyst, composition for gas diffusion electrode formation, gas diffusion electrode, membrane-electrode assembly (MEA) and fuel battery stack
JP2015195209A
Recovery method and recovery apparatus of precious metal
JP2017008340A
Manufacturing method of catalyst for electrode
JP2017041384A
Electrode catalyst for fuel cell, electrode for fuel cell including the electrode catalyst, and membrane electrode assembly and fuel cell including the same
US20140335437A1